Efficient hydrogen release from perhydro-N-ethylcarbazole using catalyst-coated metallic structures produced by selective electron beam melting - Peters, Willi; Eypasch, Martin; Frank, T.; Schwerdtfeger, Jan; Körner, Carolin; Bösmann, Andreas; Wasserscheid, Peter (Energy and Environmental Science, 2015)
A particularly suitable reactor concept for the continuous dehydrogenation of perhydro-N-ethylcarbazole in the context of hydrogen and energy storage applications is described. The concept addresses the fact that dehydrogenation is a highly endothermic gas evolution reaction. Thus, for efficient dehydrogenation a significant amount of reaction heat has to be provided to a reactor that is essentially full of gas. This particular challenge is addressed in our study by the use of a catalyst-coated (Pt on alumina), structured metal reactor obtained by selective electron beam melting. The so-obtained reactor was tested both as a single tube set-up and as a Hydrogen Release Unit (HRU) with ten parallel reactors. In stationary operation, the HRU realized a hydrogen release capacity of 1.75 kW(therm) (960 W-el in a subsequent fuel cell) with up to 1.12 g(H2) min(-1) g(Pt)(-1) and a power density of 4.32 kW(el) L-1 of HRU reactor.

Reactor for the release of hydrogen from a liquid compound. - Eypasch, Martin; Zenner, Michael; Peters, Willi; Wasserscheid, Peter (2015)
The invention relates to a reactor for releasing hydrogen from a hydrogen-bearing, liq. compd., comprising a reactor vessel, which contains at least one body having a metal support structure, to which metal support structure a solid, highly porous coating is applied, which contains catalytically active substances for the release of hydrogen from the liq., hydrogen-bearing compd. The reactor is characterized in that the body having the metal support structure can be heated by means of Joule self-heating or induction heating. [on SciFinder(R)]
Keywords: reactor hydrogen release liq energy storage compd catalytic dehydrogenation; hydrogen storage release supply tubular reactor heating porous coating